Complexation of daclatasvir by single isomer methylated β-cyclodextrins studied by capillary electrophoresis, NMR spectroscopy and mass spectrometry. (1st December 2021) - Krait, Sulaiman; Salgado, Antonio; Peluso, Paola; Malanga, Milo; Sohajda, Tamás; Benkovics, Gábor; Naumann, Lukas; Neusüß, Christian; Chankvetadze, Bezhan; Scriba, Gerhard K.E.
Abstract: In capillary electrophoresis an enantioseparation of daclatasvir (DCV) was observed in case of heptakis(2, 6-di- O -methyl)-β-CD, heptakis(2- O -methyl)-β-CD and β-CD, while two peaks with a plateau were noted for heptakis(2, 3, 6-tri- O -methyl)-β-CD and heptakis(2, 3-di- O -methyl)-β-CD indicating a slow equilibrium. Heptakis(6- O -methyl)-β-CD and heptakis(3- O -methyl)-β-CD yielded broad peaks. Nuclear magnetic resonance experiments including nuclear Overhauser effect-based techniques revealed inclusion complex formation for all CDs with the biphenyl ring of DCV within the cavity and the valine-pyrrolidine moieties protruding from the torus. However, in case of heptakis(2, 6-di- O -methyl)-β-CD, heptakis(2- O -methyl)-β-CD and β-CD higher order structures with 1:3 stoichiometry were concluded, where the valine moieties enter additional CD molecules via the secondary side. Heptakis(2, 3, 6-tri- O -methyl)-β-CD and heptakis(2, 3-di- O -methyl)-β-CD yielded primarily 1:1 complexes. Higher order complexes between DCV and heptakis(2, 6-di- O -methyl)-β-CD were corroborated by mass spectrometry. Complex stoichiometry was not the reason for the slow equilibrium yielding the plateau observed in capillary electrophoresis, but structural characteristics of the CDs especially complete methylation of the secondary rim. Highlights: The enantioseparation of daclatasvir by single isomer methylated β-CDs was studied by CE. Two peaks with a plateau in between not related to an enantioseparation was observed for 2, 3-DM-β-CD and TM-β-CD. NMR revealed the formation of 1:1 or 1:3 complexes depending on the CD substitution pattern. Higher order complexes concluded from NMR could be corroborated by ESI-MS.